2012
DOI: 10.5694/mja11.11329
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease and automatic reporting of estimated glomerular filtration rate: new developments and revised recommendations

Abstract: The publication of the Australasian Creatinine Consensus Working Group's position statements in 2005 and 2007 resulted in automatic reporting of estimated glomerular filtration rate (eGFR) with requests for serum creatinine concentration in adults, facilitated the unification of units of measurement for creatinine and eGFR, and promoted the standardisation of assays. New advancements and continuing debate led the Australasian Creatinine Consensus Working Group to reconvene in 2010. The working group recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
114
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 32 publications
(29 reference statements)
1
114
0
Order By: Relevance
“…As the CKD-EPI equation is emerging as the preferred equation in clinical laboratories for estimating GFR, 38 the examination of its performance in the drug-dosing setting is important, as ideally a single equation should be used for any scenario where an estimate of GFR is required. Most dose adjustment is concerned with patients with impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
“…As the CKD-EPI equation is emerging as the preferred equation in clinical laboratories for estimating GFR, 38 the examination of its performance in the drug-dosing setting is important, as ideally a single equation should be used for any scenario where an estimate of GFR is required. Most dose adjustment is concerned with patients with impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Once again, the better accuracy of the CKD-EPI equation is purely analytical. One of the most recent recommendations published comes from the Australasian Creatinine Consensus Working Group which recommended the use of CKD-EPI equation and a numerical expression at least up to 90 mL/min/1.73 m 2 [19]. Our study provides a basis for such recommendations and even extends it to eGFR as high as 120 mL/min/1.73 m 2 , as long as an accurate enzymatic assay is used.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, however the revised recommendations of the Australian Creatinine Consensus Group did not agree with age related reference intervals. In the study of patients with eGFRs of between 45 and 60 mL/min/1.73 m 2 and no albuminuria there was no difference in mortality from kidney disease in those above to those below 65 years [13]. However, Roderick [14] has shown that older patients ([75) commonly had eGFRs \60 mL/min/1.73 m 2 but there did not appear to be associated adverse pathophysiologic consequences until the eGFR fell to less than 45 mL/min/1.73 m 2 .…”
Section: Introductionmentioning
confidence: 99%